Evaluation of Phytochemicals And Antioxidant Activity (IC50) of Bintaro Fruit Ethanol Extract (Cerberaodollam L.) - Sutrisno Adi Prayitno; Lilla Puji Lestari; Dwi Retnaningtyas Utami; Nadhifah Salsabila (Universitas Dr Soetomo, 2021)
The phytochemical compounds in bintaro fruit can be used as herbs to maintain health. The compounds that play a role are flavonoids and phenols. These two compounds can be used as a reference for measuring the level of antioxidant activity in natural materials. There is a correlation between total phenols, total flavonoids, and antioxidants (IC50) found in natural ingredients. The purpose of this study was to determine the total phenol content, flavonoids, and antioxidant activity in the ethanol extract of Bintaro fruit. Bintaro fruit was extracted using ethanol solvent by maceration method which was then evaporated with a rotary evaporator on the obtained macerate. The extract obtained was then analyzed for levels of total flavonoids, total phenols, and antioxidants (IC50). Ethanol extract of bintaro fruit in the study produced total phenol content of 73.04 mg GAE/g extract, flavonoids 41.61 mg QE/g extract and had antioxidant activity (IC50=275.06 ppm). Recommended for in vivo or in vitro assay for certain diseases using these extracts.Further research is needed with the use of other solvent to see optimall in the screening of active compounds.